Victim, Violent, Vulnerable: a Feminist Response to the Incel Radicalisation Scale - Kelly, Megan (Perspectives on terrorism, 2024)
Following several deadly attacks in recent years, misogynist incels have piqued academic interest. However, attempts by terrorism scholars to understand incels’ radicalisation, ideology, and mental health raise concerns. In this article, we illustrate these concerns with the example of the Incel Radicalisation Scale (IRS), which relies on survey data and claims to help identify, measure, and prevent radicalisation among incels. First, drawing on a growing feminist knowledge base on incels and male supremacy, masculinity, and violence, we question the definition of core concepts (radicalisation, violence, misogyny) and incels in the IRS. Second, we criticise the methods used for sampling and concept validation, including reliance on incels’ self-representation and the dismissal of their harmful online activity. Third, we assess what these shortcomings mean for the IRS’ conclusions regarding the violent potential of incels, and the role of mental health and misogyny for male supremacist incel movements. We argue such conclusions are prone to legitimising misogynist incel narratives of victimhood, and overlooking broader harms such as normalising misogynist violence and male and white supremacism. We therefore caution against using the IRS and emphasise the importance of having a comprehensive picture of incel radicalisation. Future studies must be more rigorous about addressing the problematic effects resulting from research designs of uncritical epistemologies in male supremacist research.